Nie przeoczyć teraz – filozofia codzienności Janusza Korczaka - Sylwester Zielka (Problemy Wczesnej Edukacji)
In this paper, I focus on one of the children’s rights, which Janusz Korczak raised in his writings, namely the child’s right to the present day, which I understand as a postulate to appreciate the dignity of a child in its everyday life. My aim in this paper is, therefore, not only to reconstruct and uncover the complexities of this postulate, but also to theoretically embed this concept in pedagogical narratives about the child, and more specifically in anthropology of education and upbringing. In order to achieve this aim, 1. I will describe two paths in thinking about the relationship between human beings and their culture, taking into account especially its temporal dimension. Then I will proceed to 2. the concept of children’s rights in Korczak’s understanding of the child subjectivity; in order to indicate 3. the radical and ethical character of message his thinking.